Efektivitas Penggunaan Aplikasi KAI ACCESS Dalam Meningkatkan Kualitas Pelayanan PT. KAI (Studi Pada Stasiun Gubeng) - Izzati, Najma Laily; Hayat, Hayat; Rahmawati, Septina Dwi (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
(Effectiveness of Using KAI ACCESS Application in Improving the Quality of PT KAI Services (Study at Gubeng Station) The government as the holder of the people's trust in achieving a prosperous life has a big role and responsibility in organizing and implementing supporting programs to achieve a prosperous life and fulfilling job opportunity quotas in Indonesia. The Balikpapan City Manpower Office, which has responsibility for carrying out mandatory employment matters, strives to ensure that local job seekers can compete in the job market by increasing their competency. This research aims to analyze the strategy of the Balikpapan City Manpower Office in improving the competence of local job seekers as well as the obstacles faced by the Balikpapan City Manpower Office. This research is a mixed methods research method with a research focus on strategies for increasing the competence of local job seekers through analysis of the internal environment of strengths and weaknesses , analysis of the external environment of opportunities and threats and the obstacles faced by the Balikpapan City Employment Service. The results of the research show that the strengths of the Balikpapan City Manpower Office are: 1) Plan Work structured , 2) Regulation employment , 3) Facilities and infrastructure . The weaknesses of the Balikpapan City Manpower Office are : 1 ) Lack of human resources, 2) Limitations budget , 3) There is no UPTD BLK for Balikpapan City. The opportunities that the Balikpapan City Manpower Office has are : 1) Development technology , 2) The existence of private LPK , 3) The existence of owned BLK Province East Kalimantan , 4) Training Institute belonging to the Ministry, 5) Apprenticeship . The threats faced by the Balikpapan City Manpower Office are : 1 ) Immigrants from outside area , 2) Expensive cost training Work . Meanwhile, the obstacles faced by the Balikpapan City Manpower Office originate from job seekers who are not serious about improving their competence and the limitations of LPKs in Balikpapan City both in terms of numbers and quality standards.. Abstrak Pemerintah sebagai pemegang amanah rakyat pada pencapaian kehidupan yang sejahtera memiliki andil dan tanggung jawab besar dalam mengatur serta melaksanakan program-program pendukung agar tercapainya kehidupan yang sejahtera dan terpenuhinya kuota-kuota peluang kerja di negara Indonesia. Disnaker Kota Balikpapan yang memiliki tanggung jawab dalam melaksanakan urusan wajib ketenagakerjaan berupaya agar pencari kerja lokal dapat bersaing di pasar kerja dengan meningkatkan kompetensinya. Penelitian ini bertujuan menganalisis strategi Disnaker Kota Balikpapan dalam meningkatkan kompetensi para pencari kerja lokal serta kendala yang dihadapi Disnaker Kota Balikpapan. Penelitian ini merupakan metode penelitian mixed methods dengan fokus penelitian strategi peningkatan kompetensi para pencari kerja lokal melalui analisis lingkungan internal strenght dan weakness, analisis lingkungan eksternal opportunity dan threat serta kendala yang dihadapi Dinas Ketenagakerjaan Kota Balikpapan. Hasil penelitian menunjukkan strenght (kekuatan) yang dimiliki Disnaker Kota Balikpapan yaitu : 1) Rencana kerja terstruktur, 2) Regulasi ketenagakerjaan, 3) Sarana dan prasarana. Weakness (kelemahan) yang dimiliki Disnaker Kota Balikpapan yaitu : 1) Kurangnya SDM, 2) Keterbatasan anggaran, 3) Belum adanya UPTD BLK Kota Balikpapan. Opportunity (peluang) yang dimiliki Disnaker Kota Balikpapan yaitu :1) Perkembangan teknologi, 2) Keberadaan LPK Swasta, 3) Keberadaan BLK milik Provinsi Kaltim, 4) Lembaga Pelatihan milik Kementerian, 5) Pemagangan. Adapun threat (ancaman) yang dihadapi Disnaker Kota Balikpapan yaitu : 1) Pendatang dari luar daerah, 2) Mahalnya biaya pelatihan kerja. Sementara itu, kendala yang dihadapi oleh Disnaker Kota Balikpapan yaitu berasal dari dalam diri pencari kerja yang tidak serius untuk meningkatkan kompetensi dirinya serta keterbatasan LPK di Kota Balikpapan baik dari jumlahnya maupun standar mutu yang dimiliki.